The Role of G Protein-Coupled Receptors in the Right Ventricle in Pulmonary Hypertension - Viswanathan, Gayathri; Mamazhakypov, Argen; Schermuly, Ralph T.; Rajagopal, Sudarshan (Frontiers in Cardiovascular Medicine, 2018)
Pressure overload of the right ventricle (RV) in pulmonary arterial hypertension (PAH) leads to RV remodeling and failure, an important determinant of outcome in patients with PAH. Several G protein-coupled receptors (GPCRs) are differentially regulated in the RV myocardium, contributing to the pathogenesis of RV adverse remodeling and dysfunction. Many pharmacological agents that target GPCRs have been demonstrated to result in beneficial effects on left ventricular (LV) failure, such as beta-adrenergic receptor and angiotensin receptor antagonists. However, the role of such drugs on RV remodeling and performance is not known at this time. Moreover, many of these above mentioned receptors are also expressed in the pulmonary vasculature, which could result in complex effects in PAH. This manuscript reviews the role of different GPCRs in RV remodeling and dysfunction and discusses the potential of targeting such signaling in the RV to attenuate remodeling while promoting improvements of RV function in PAH.